The Psychological and Pedagogical Foundations of Developing Cultural Identification in Art Education - Toshmuhammedova Iroda Alibek qizi (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
This article explores the psychological and pedagogical foundations of developing cultural identification in art education. Cultural identification in students enhances their understanding of personal and collective identity, fosters aesthetic and ethical awareness, and strengthens socio-cultural competence. The study examines methods for integrating cultural themes, art analysis, and interactive pedagogical strategies to promote cultural awareness, creativity, and reflective thinking among students.